2005
DOI: 10.1159/000088279
|View full text |Cite
|
Sign up to set email alerts
|

Applying an Artificial Neural Network to Predict Total Body Water in Hemodialysis Patients

Abstract: Background: Estimating total body water (TBW) is crucial in determining dry weight and dialytic dose for hemodialysis patients. Several anthropometric equations have been used to predict TBW, but a more accurate method is needed. We developed an artificial neural network (ANN) to predict TBW in hemodialysis patients. Methods: Demographic data, anthropometric measurements, and multifrequency bioelectrical impedance analysis (MF-BIA) were investigated in 54 patients. TBW measured by MF-BIA (TBW-BIA) was the refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…Clinical studies have suggested the superiority of ANN, as compared to other statistical models, for the classification or prediction of morbidity [15,16]. The ability of the ANN to process more information in the context of multidimensionality of complex data to a large extent explains the superiority of ANN as a predicting model.…”
mentioning
confidence: 99%
“…Clinical studies have suggested the superiority of ANN, as compared to other statistical models, for the classification or prediction of morbidity [15,16]. The ability of the ANN to process more information in the context of multidimensionality of complex data to a large extent explains the superiority of ANN as a predicting model.…”
mentioning
confidence: 99%
“…However, we selected only six variables that are usually measured in hemodialysis patients. Our reason is that for any forecasting model to be useful in making clinical decisions, it should use only parameters that are readily available to the clinician at the time of triage (Chiu et al 2005). This is an essential issue since fewer inputs may simplify the process for clinicians in determining subsequent decisions rapidly (Bates et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…An artificial neural network (ANN) is a connectionist model composed of non-linear computational elements called 'neurons or axons' arranged in highly interconnected layers with a structure that simulates the transfer of information through the nervous system (8). By changing the transfer functions and the associated parameters, this constructed neural network adapts itself to the pattern of the input variables and eventually generates numbers that iteratively solves to values of the designated output variables (9).…”
Section: Introductionmentioning
confidence: 99%